CONCEPTUAL REVIEW OF MICROFINANCE AND SUSTAINABLE DEVELOPMENT A PROSPECT OF ISLAMIC BANKING MICROFINANCE IN NIGERIA - Abdullahi Isah; Moh’d Rizal bin Muwazir (Universitas Nahdlatul Ulama Surakarta, 2026)
This study presents a conceptual review examining the role of Islamic banking microfinance facilities in poverty alleviation in Nigeria. Islamic financial institutions have become an integral component of the modern global economy and operate under similar economic principles as conventional financial systems, while maintaining distinctive ethical and Sharia-based foundations. Over the past decade, Islamic microfinance has demonstrated significant potential in promoting financial inclusion and reducing poverty, particularly among low-income communities in Nigeria. Unlike conventional microfinance, which is largely interest-based and may involve elements of uncertainty, Islamic microfinance operates on profit-and-loss sharing and asset-backed financing principles derived from the Holy Qur’an and Sharia law. Islamic banks provide various microfinance instruments, including Musharakah, Mudarabah, Murabaha, Ijarah, and Qard Hasan, each characterized by transparency, real asset valuation, and clearly defined contractual obligations. These features encourage productive economic activities and facilitate the circulation of wealth among the poor. This paper adopts a conceptual framework based on library research and secondary data, drawing from relevant literature on Islamic microfinance, sustainable development, and poverty alleviation. The study highlights the relevance of Islamic microfinance as a sustainable and ethical financial alternative for addressing poverty challenges in Nigeria.